Design & development of a novel house hold compressing device for a wheelie bin - Rehman, Fayyaz; Burman, Blake (Cranfield University Press, 2013)
This project consists of researching, designing, developing, prototyping and testing a device that clamps onto a wheelie bin and easily compresses the waste inside. Once attached, by pulling on the lever, the device will compress the contents inside allowing for disposal of more waste. The design is easily assembled, light and sturdy enough so that any household individual can use it. Prototype testing was performed to identify the required forces necessary to compress a sufficient amount of waste and identifying which materials or types of waste can be compressed. The prototype testing showed that the device is capable of compressing the normal household wastes (compressing plastic bottles, cardboards, tin cartons) up to 45% off the original volume. The paper discusses the design, development and testing of this device to appreciate the proof of the concept as well as discussing it in terms of saving the cost of recycling as well.
Keywords: Household waste; Recycling; Compressing Device